Integrating risk, the Good Lives Model and recovery for mentally disordered sexual offenders. Issue 1 (2nd January 2016) - Lord, Alex
Abstract: Personality disordered and mentally disordered sexual offenders (MDSOs) with complex diagnoses such as schizophrenia, developmental disorders and mood disorders face challenges of restoring their mental health, living more safely with personality- and offence-related risks, while addressing concerns about their capacity to reintegrate into society; this has been termed "secure recovery". This paper reviews the literature on recovery, demonstrating its commonality with the Good Lives Model (GLM) as applied to MDSOs' offending treatment. GLM appears to provide a better fit with the recovery needs of MDSOs than the Risk–Need–Responsivity model because it emphasises approach goals, enhanced responsivity and skills acquisition. Recovery needs to integrate coping with mental disorders with risk management and a healthy, future lifestyle. Both secure recovery and GLM support the need for client–clinician collaboration, promoting self-determination and a shared narrative about coping with enduring risk and the hope of sustained well-being.